Conversión alimenticia en Cuyes Colorados en etapa de crecimiento con una tercera Progenie de Cruce Genético de Tipo absorbente. - Vilcasana Flores, Irma Gissela (2017)
The guinea pig production in Ecuador is concentrated in the Sierra Region, this production is very important in the livestock economy, on the other hand, it has not been possible to establish an own Ecuadorian line with genetic characteristics suitable for the means of production. This project aimed to determine the feed conversion of red guinea pigs in the growing stage with a third genetic crossbreed progeny of absorbent type, developed in the guinea pigs project of the Experimental and Production Center Salache (CEYPSA), it was started by verifying the selection characteristics with animals of the second progeny, evaluating between the two progenies from the record weights applying comparative analysis to evaluate the absorbent crossing. This project identified 5 categories in the growing stage and 2 categories in red guinea pigs of third progeny when applying ADEVA and DUNCAN statistical analyzes, then the category results of growing guinea pigs were related to a minimum general weight of 26 grams and maximum of 513.80 grams during 10 weeks. Consequently, it is necessary to talk about the consumption of food generated in this time the parameters the consumption of food of fresh forage with a minimum average of 1736.40 g and a maximum of 2875.80 g in colored guinea pigs (females and males) in the stage of growth. Consequently the parameters of food consumption generated at this time: fresh forage with a minimum average of 1736.40 grams and a maximum of 2875.80 grams in colored guinea pigs (females and males) in the growing stage. Finally the general food conversion in red guinea pigs gives a maximum value of 11.46% and minimum of 5.61%. Concluding that the animals with better feed conversion in this stage are female and male colored guinea pigs with a conversion average of 7.5 being notorious that guinea pigs of this color do not fully comply with this aspect. In conclusion, a negative - zero correlation (-0.08) was found between the weight data of progeny 1 and 3 and the comparison between progenies 2 and 3 showed a very weak correlation (0.11). Finally, a negative - zero correlation (-0.08) was found between the weight data of progeny 1 and 3, on the other hand the comparison between progenies 2 and 3 had a negative correlation - very weak (0.11).